WOMEN IN REPRODUCTIVE SCIENCE: Lessons from bioengineering the ovarian follicle: a personal perspective. Issue 6 (December 2019) - Woodruff, Teresa K
Abstract : The ovarian follicle and its maturation captivated my imagination and inspired my scientific journey – what we know now about this remarkable structure is captured in this invited review. In the past decade, our knowledge of the ovarian follicle expanded dramatically as cross-disciplinary collaborations brought new perspectives to bear, ultimately leading to the development of extragonadal follicles as model systems with significant clinical implications. Follicle maturation in vitro in an 'artificial' ovary became possible by learning what the follicle is fundamentally and autonomously capable of – which turns out to be quite a lot. Progress in understanding and harnessing follicle biology has been aided by engineers and materials scientists who created hardware that enables tissue function for extended periods of time. The EVATAR system supports extracorporeal ovarian function in an engineered environment that mimics the endocrine environment of the reproductive tract. Finally, applying the tools of inorganic chemistry, we discovered that oocytes require zinc to mature over time – a truly new aspect of follicle biology with no antecedent other than the presence of zinc in sperm. Drawing on the tools and ideas from the fields of bioengineering, materials science and chemistry unlocked follicle biology in ways that we could not have known or even predicted. Similarly, how today's basic science discoveries regarding ovarian follicle maturation are translated to improve the experience of tomorrow's patients is yet to be determined.